EXTRACTION OF THE CAROTENOID LYCOPENE FROM CHONTO TOMATO (Lycopersicum esculentum) - CARDONA, Eliana M.; RÍOS, Luis A.; RESTREPO V., Gloria M. (Vitae, 2009)
Lycopene, to which tomato owes its red coloration, besides presenting great properties like colorant, is a powerful antioxidant that helps to combat degenerative diseases. Due to the importance that has been given to lycopene, because of its properties, in this investigation both steam-dragging and solvent extraction methods are compared based on the obtained yield and the pre-treatment given to the vegetable sample, characterizing the obtained extracts by means of visible UV spectrometry. Extractions are also carried out to determine the lycopene content in tomato chonto Lycopersicum esculentum, as well as other parameters of the extraction process: temperature, ratio mass of tomato pulp to solvent volume, time of extraction and number of stages. With these parameters, a basic design of a pilot plant is proposed for the extraction of this carotenoid, arranging the equipment according to the corresponding flow diagram and under the necessary operation conditions to avoid the degradation and decomposition of lycopene along the process and that allow to obtain a yield of 6 g of oleoresin / Kg of pulp.